Studi Literatur Hubungan Kepercayaan Diri dengan Komunikasi Matematika Pada Siswa Sekolah Menengah Pertama - Elsa Yanti Simorangkir; Nadia Arlisa Putri; Nazwa Nabila; Sintia Safitri (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to review the literature on the relationship between self-confidence and mathematical communication skills of junior high school students. The method used is a literature review with a qualitative-descriptive approach. The data sources in this study are national scientific journal articles relevant to the topic, published from 2021 to 2025. The data analysis technique was carried out through content analysis, which included the stages of journal collection, article selection based on topic relevance, and systematic conclusion drawing. The following are the findings obtained from the literature review: 1) There is a positive relationship between self-confidence and students’ mathematical communication skills at the junior high school level, where the higher the students’ level of self-confidence, the better their mathematical communication ability. 2) Students with high self-confidence are better able to fulfill all mathematical communication indicators optimally, including the ability to use mathematical symbols accurately, construct mathematical models appropriate to the problem, explain problem-solving steps systematically, and convey conclusions in understandable language. 3) Conversely, students with low self-confidence tend to be passive, experience psychological barriers, and have difficulty expressing mathematical ideas both verbally and in writing.